2003
DOI: 10.1017/s0950268803008446
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of measles in Addis Ababa, Ethiopia: implications for control through vaccination

Abstract: We undertook a representative survey of measles antibodies in Addis Ababa, Ethiopia 1994, to characterize immunity and transmission. Specific-antibody levels (IU/l) were determined by ELISA for 4654 sera from individuals aged 0-49 years (1805 <15 years) collected by stratified household-cluster sampling. The proportion seronegative (<100 IU/l) was 20 % (95 % CI : 16-25) in children 9-59 months old, declining to 9 % (7-12) in 5-9 year olds, 5 % (4 -7) in 10-14 year olds, and <1% in adults. The proportion of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…15,17 This is in view of the fact that studies have shown that about four in five children develop protective antibody levels when the measles vaccine is administered at nine months of age, and nearly all have a protective antibody response after vaccination at 12 months of age. 18,19 Monthly distribution showed higher frequencies during the dry seasons. This is in keeping with previous observations by earlier studies.…”
Section: Discussionmentioning
confidence: 97%
“…15,17 This is in view of the fact that studies have shown that about four in five children develop protective antibody levels when the measles vaccine is administered at nine months of age, and nearly all have a protective antibody response after vaccination at 12 months of age. 18,19 Monthly distribution showed higher frequencies during the dry seasons. This is in keeping with previous observations by earlier studies.…”
Section: Discussionmentioning
confidence: 97%
“…Several authors demonstrated that vaccinated individuals have lower GMT compared with those acquiring immunity through natural infection [9,10,[15][16][17]19,[24][25][26]30,34,69,96,99]. There was insufficient information provided to determine if certain vaccination programmes resulted in a lower GMT.…”
Section: Major Findings Of the Reviewmentioning
confidence: 99%
“…In the pre-vaccine era, measles was primarily concentrated in school-aged children in the industrialized world [3]. Developing countries tend to be characterized by an even lower mean age at infection, which is important as disease severity and case-fatality rates are higher in younger children [46]. …”
Section: Introductionmentioning
confidence: 99%